Loss of Tbk1 kinase activity protects mice from diet-induced metabolic dysfunction - Victoria H. Cruz; Emily N. Arner; Katherine W. Wynne; Philipp E. Scherer; Rolf A. Brekken (Elsevier, 2018)
Objective: TANK Binding Kinase 1 (TBK1) has been implicated in the regulation of metabolism through studies with the drug amlexanox, an inhibitor of the IκB kinase (IKK)-related kinases. Amlexanox induced weight loss, reduced fatty liver and insulin resistance in high fat diet (HFD) fed mice and has now progressed into clinical testing for the treatment and prevention of obesity and type 2 diabetes. However, since amlexanox is a dual IKKε/TBK1 inhibitor, the specific metabolic contribution of TBK1 is not clear. Methods: To distinguish metabolic functions unique to TBK1, we examined the metabolic profile of global Tbk1 mutant mice challenged with an obesogenic diet and investigated potential mechanisms for the improved metabolic phenotype. Results and conclusion: We report that systemic loss of TBK1 kinase function has an overall protective effect on metabolic readouts in mice on an obesogenic diet, which is mediated by loss of an inhibitory interaction between TBK1 and the insulin receptor. Keywords: TBK1, IKKε, Obesity, Insulin, Insulin resistance, Metabolism